Stylistics of Audiovisual Texts: Linguistic, Semiotic, and Pragmatic Approaches - Bozorova , Vasila Ilkhomovna (The Lingua Spectrum, 2026)
Audiovisual texts constitute a complex mode of communication in which meaning emerges from the interaction of verbal language, visual imagery, and sound. This paper deals with the issues based on the stylistics of audiovisual texts from linguistic, semiotic, and pragmatic perspectives, emphasizing the role of stylistic devices across multiple communicative channels. It explores how lexical choices, syntactic structures, and pragmatic strategies are influenced by the multichannel nature of audiovisual discourse and how these elements shape meaning, enhance audience engagement, and ensure communicative effectiveness. Adopting an interdisciplinary framework that draws on translation studies, multimodal discourse analysis, and pragmatics, the study argues that audiovisual stylistics cannot be sufficiently explained through purely linguistic approaches. Instead, a holistic perspective is required to capture the dynamic interplay between language, image, sound, and context. As well as, the findings underscore the significance of stylistic awareness for audiovisual translation, localization practices, and media analysis within an increasingly globalized communication environment.